Pemodelan Sistem Pakar Diagnosis Penyakit pada Tanaman Tembakau Virginia dengan Metode Dempster-Shafer - Chandra Tio Pasaribu; Nurul Hidayat; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Knowladge of the nature of the pathogen, symptoms of disease, as well as the factors that influence the development of plant diseases is one of the important things that should be known to determine the appropriate control methods for pathogen targeted. The lack of knowledge possessed by farmers and the lack of consultation with Virginia's Tobacco plant experts has caused farmers to experience delays in handling the affected plants. So, on the problems of Virginia Tobacco plants can be with the creation of an expert system. The method used is Dempster-Shafer is a theory that is capable of handling various possibilities that combine one possibility with existing facts. The Dempster-Shafer theory is based on belief function and plausible reasoning used to combine separate pieces of information to calculate the probability of an event. In this study there are 9 types of disease in Virginia Tobacco plant with input system in the form of facts that occur in Virginia Tobacco plants. Based on the data used obtained accuracy value of 84.6% so it can be concluded the system goes well.